Sound absorption of palm coir fiber - Rahmad, R.; Ahmad Sukri, A. S. (UTHM Publisher, 2018)
This research was conducted to study acoustic characteristic of palm coir fibre, which has high potential to be use for sound absorbing material. The sample was tested with different weight ratio. The weight ratio of palm coir fibre varied from 30 gm to 60 gm with 20 mm thickness. The samples were deformed by using the mould that was invented by using PVC pipe. These sample were tested by using Impedance tube according to international standard, ASTM E1050-98 used for measuring the sound coefficients. While for density and porosity test, the sample was tested according to international standard ASTM D792. The results showed sound absorption coefficients of palm coir fibre were good from 350 Hz to 2000 Hz within the range 0.65 dB – 0.90 dB for Impedance tube. Results obtained for density and porosity test, also were good from 30gm and 60gm respectively. Overall, the optimum, sound absorption coefficient was obtained from weight 40gm. These results indicate that palm coir fibre is promising to use as raw material of sound absorbing material with low cost, light and biodegradable.